2020
DOI: 10.1634/theoncologist.2020-0161
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib and Nivolumab or Pembrolizumab Combination and Circulating Tumor DNA Response Assessment in Refractory Microsatellite Stable Colorectal Cancer

Abstract: Background Metastatic colorectal cancers (MCRCs) with microsatellite stability (MSS) are resistant to immunotherapy with programmed cell death protein 1 (PD‐1) and programmed death‐ligand 1 inhibitors. However, the addition of regorafenib to nivolumab was recently associated with a high response rate and a protracted progression‐free survival in a small cohort of MSS Japanese patients with metastatic colorectal cancer. Materials and Methods We evaluated the outcome of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 25 publications
4
80
0
Order By: Relevance
“…Regorafenib (80 mg) has been proven the recommended doses to add to nivolumab in the expanded cohort. Although toxicity was similar to the Japanese study REGONIVO, very modest efficacy was reported with no objective responses [122]. Intrinsic genetic differences between the Asian and the Caucasian populations have been suggested as an explanation for these heterogeneous results, though in the absence of a clear functional hypothesis [29].…”
Section: Anti-tams + Immune Checkpoint Inhibitorssupporting
confidence: 57%
See 2 more Smart Citations
“…Regorafenib (80 mg) has been proven the recommended doses to add to nivolumab in the expanded cohort. Although toxicity was similar to the Japanese study REGONIVO, very modest efficacy was reported with no objective responses [122]. Intrinsic genetic differences between the Asian and the Caucasian populations have been suggested as an explanation for these heterogeneous results, though in the absence of a clear functional hypothesis [29].…”
Section: Anti-tams + Immune Checkpoint Inhibitorssupporting
confidence: 57%
“…Safety data were consistent across these studies highlighting that regorafenib at the dose of 160 mg was associated with a high incidence of severe adverse events [28,36,121,122]. This is not surprising in the light of the escalating flexible dosing approach currently recommended and widely adopted in the daily clinical practice.…”
Section: Anti-tams + Immune Checkpoint Inhibitorssupporting
confidence: 52%
See 1 more Smart Citation
“…Many centers all over the world are adopting the combination of regorafenib and ICI with a compassionate purpose for patients. However, a recent retrospective study of 18 patients including five Asians in a USA cancer center failed to reveal comparable clinical activity of regorafenib plus nivolumab (11). The authors proposed that this combination strategy should be avoided in clinical practice especially in pMMR/MSS mCRC patients with liver metastases (11).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent retrospective study of 18 patients including five Asians in a USA cancer center failed to reveal comparable clinical activity of regorafenib plus nivolumab (11). The authors proposed that this combination strategy should be avoided in clinical practice especially in pMMR/MSS mCRC patients with liver metastases (11). Obviously, more evidence assessing this combination strategy is needed before the completion of conclusive Phase III studies.…”
Section: Introductionmentioning
confidence: 99%